2021
DOI: 10.1039/d0ra08803j
|View full text |Cite
|
Sign up to set email alerts
|

Liquid fuel from waste tires: novel refining, advanced characterization and utilization in engines with ethyl levulinate as an additive

Abstract: Proposed novel upgrading method for crude tire pyrolysis oil for utilization in diesel engines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“…During the pyrolysis process, the organic volatile matter of tires, mainly the rubber polymers, are decomposed to lower molecular weight products, oils, and gases, while the inorganic compounds and the nonvolatile carbon black, contained in the waste tire, remain as solid char residue [10]. Many research groups have demonstrated that pyrolytic oils can be used as fuels [11][12][13][14][15][16] or chemical feedstock [17][18][19], the gas can be used as a process fuel [20][21][22][23], and the char has the potential to be used as carbon black or activated carbon (AC) [24][25][26]. The yields and characteristics of pyrolysis products depend on the waste tires feedstock (composition and particle size) and the operating parameters, such as temperature, heating rate, vapors/solid residence time, and atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…During the pyrolysis process, the organic volatile matter of tires, mainly the rubber polymers, are decomposed to lower molecular weight products, oils, and gases, while the inorganic compounds and the nonvolatile carbon black, contained in the waste tire, remain as solid char residue [10]. Many research groups have demonstrated that pyrolytic oils can be used as fuels [11][12][13][14][15][16] or chemical feedstock [17][18][19], the gas can be used as a process fuel [20][21][22][23], and the char has the potential to be used as carbon black or activated carbon (AC) [24][25][26]. The yields and characteristics of pyrolysis products depend on the waste tires feedstock (composition and particle size) and the operating parameters, such as temperature, heating rate, vapors/solid residence time, and atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of aryl halides for arylation of amines using catalysts based on copper as a cheap and biogenic element potentially enables simple and safe destruction (dehalogenation) of waste non-biodegradable aryl halides to the corresponding aryl amines. Produced aromatic amines could be suitable for subsequent utilization as synthetic intermediates or for energy utilization as the refuse-derived fuel (RDF) [119]. The main advantage of the possible utilization of mentioned C-N cross-coupling reactions compared to C-C or C-O couplings is the minimization of the risk of the potential undesirable formation of highly toxic and thermodynamically stable polyhalogenated biphenyls, dibenzo-p-dioxins, or dibenzofurans as the by-products of arylation reactions [120].…”
Section: Discussionmentioning
confidence: 99%
“…Em Lei et al, (2016) e Mohan et al, (2021), verificaram que o consumo específico de diesel, o consumo de energia e emissões de gases foram menores com as misturas de diesel e levulinato de etila, sugerindo maior eficiência de conversão de combustível para as misturas de combustível e a capacidade promissora do levulinato para o meio ambiente. Além disso, os LEV como aditivos de combustíveis facilitam a combustão completa, devido à maior oxigenação de sua cadeia, conduzindo a uma combustão completa com menor emissão de gases poluentes (Nelson et al, 2022).…”
Section: Tabela 1 -Propriedades De Combustível Jet A-1 Puro E Em Mist...unclassified